THE IMPACT OF MOBILE TECHNOLOGY (BYOD) AND THE USE OF AUTHENTIC VIDEO MATERIALS ON STUDENTS’ LEARNING EFFECTIVENESS - Skrylnikova, Olga; Belyakova, Tatiana; Dolzhenkov, Valeriy; Shugaeva, Ekaterina; Romanovich, Vera; Vasyukov (Revista Inclusiones, 2020)
The study is aimed at testing the effectiveness of using authentic video materials in mobile learning in the formation of English lexical competence of future managers in the field of hospitality and services. The article analyses the concept of mobile learning and its nature. It presents the results of the formation of professionally oriented English lexical competence in speaking in mobile learning using authentic video materials. The results are based on experimental research. It has been proved that the effectiveness of the formation of professionally oriented English lexical competence in speaking is high if mobile learning is organized using authentic video materials.